2020
DOI: 10.1111/basr.12214
|View full text |Cite
|
Sign up to set email alerts
|

Leaders do not emerge from a vacuum: Toward an understanding of the development of responsible leadership

Abstract: The worldwide problem of corruption is one that requires greater knowledge about responsible leadership. Based on the literature on responsible leadership, developmental psychology, and moral development, the purpose of our study is to understand the constructions of the motivational drivers behind the behaviors of a responsible leader. Using biographical and narrative methodologies, we analyzed the individual motivational drivers of Carlos Cavelier, a recognized responsible leaders who grew up and works in Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Based on the findings of Maak and Stoetter (2012), Van de Loo (2006), and Castillo et al (2020, 2022, three contextual similarities in the development of responsible leaders in Latin America were found. First, all the studied responsible leaders had role models who influenced their ethical and moral character from an early life stage.…”
Section: Characteristics Referencesmentioning
confidence: 97%
See 4 more Smart Citations
“…Based on the findings of Maak and Stoetter (2012), Van de Loo (2006), and Castillo et al (2020, 2022, three contextual similarities in the development of responsible leaders in Latin America were found. First, all the studied responsible leaders had role models who influenced their ethical and moral character from an early life stage.…”
Section: Characteristics Referencesmentioning
confidence: 97%
“…The authors combine the ideas about RL (Maak & Pless, 2006;Pless, 2007), psychological development (Bronfenbrenner & Morris, 2006;Magnusson & Stattin, 2006), and moral development (Kohlberg, 1981) to analyze the development of the motivational drivers of Cavelier as a responsible leader throughout his life. Castillo et al (2020Castillo et al ( , 2022 found in Cavelier motivational drivers such as the need for exploration and affirmation, the need for attachment and affiliation, the need for justice, the need for recognition, and the sense of care, which seem to explain his RL roles as steward, citizen, servant, visionary, coach, architect, storyteller, and change agent.…”
Section: Characteristics Referencesmentioning
confidence: 99%
See 3 more Smart Citations